EFFECT OF THREE OKRA HYBRIDS TO SPRAY WITH BRASSINOLIDE AND THIDIAZURON ON SOME GROWTH AND YIELD TRAITS UNDER PROTECTED CULTIVATION CONDITIONS - Al-Dulime , Meaad L A Al-Dulime; Almohammedi , Omar H. M. Almohammedi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This experiment was conducted at one of the plastic houses at the research station of College of Agriculture - Anbar University at Ramadi city, Al-Bu’itha region, during Tow season 2021-2022 and 2022-2023, to determine the response of three okra hybrids (V1, V2 and V3) to application of growth regulators Brassinolide (BR) (T0, T1 and T2) and Thidiazuron (TDZ) (T3 and T4) to various growth and yield characteristics. The experiment was conducted using RCBD Within split plot design and three replicates, The hybrid Abeer exhibited a significant superiority over other hybrids in plant height (107.80 and 111.62 cm), number of lateral branches (8.37 and 9.71 branches plant-1), number of leaves (128.39 and 133.21 leaf plant-1), leaf area (206.2 and 211.6 cm2), pod weight (5.18 and 5.17 g), and plant yield (294.2 and 512.6 g plant-1). The results indicated that treatments T2 (application of Brassinolide at a concentration of 0.2 mg L-1) and T4 (application of Thidiazuron at a concentration of 2 mg L-1) exhibited superiority across all evaluated traits. Moreover, the interaction between experimental factors positively influenced traits in treatments V1T2 and V1T4, Which demonstrated a synergistic effect.